How to reach and teach all students in the inclusive classroom : ready-to-use strategies, lessons, and activities for teaching students with diverse learning needs - Rief, Sandra F.; Heimburge, Julie A. (West Nyack, N.Y. : Center for Applied Research in Education, 1996)
Reaching all students through their multiple intelligences and learning styles. Learning developmentally. Increasing home/school communication and parent involvement. Behavior management and positive discipline. Getting students organized for success: home and school strategies...
Keywords: Education; Teaching; Mainstreaming in education -- United States; Primary school teaching -- United States; Cognitive styles in children -- United States; Lesson planning -- United States; Motivation in education -- United States; Learning disabled children -- Education -- United States